A Type IA DNA/RNA Topoisomerase with RNA Hydrolysis Activity Participates in Ribosomal RNA Processing. Issue 20 (18th September 2020) - Rani, Phoolwanti; Kalladi, Shashwath Malli; Bansia, Harsh; Rao, Sandhya; Jha, Rajiv Kumar; Jain, Paras; Bhaduri, Tisha; Nagaraja, Valakunja
Abstract: Topoisomerases maintain topological homeostasis of bacterial chromosomes by catalysing changes in DNA linking number. The resolution of RNA entanglements occurring in the cell would also require catalytic action of topoisomerases. We describe RNA topoisomerase and hydrolysis activities in DNA topoisomerase I (topo I) from mycobacteria. The interaction of topo I with mRNA, tRNA and rRNA suggested its role in some aspect of RNA metabolism; the enzyme participates in rRNA maturation via its RNA hydrolysis activity. Accumulation of rRNA precursors in a topo I knockdown strain and the rescue of rRNA processing deficiency in RNaseE knockdown cells by topo I expression indicated the enzyme's back-up support to RNases involved in rRNA processing. We demonstrate that the active-site tyrosine of the enzyme mediates catalytic reactions with both DNA/RNA substrates, and RNA topoisomerase activity can follow two reaction paths in contrast to its DNA topoisomerase activity. Mutation in the canonical proton relay pathway impacts DNA topoisomerase activity whilst retaining activity on RNA substrates. The mycobacterial topo I thus exemplifies the resourcefulness and parsimony of biological catalysis in harnessing the limited chemical repertoire at its disposal to find common solutions to mechanistically related challenges of phosphodiester breakage/exchange reactions in DNA and RNA that are essential for cell survival. Graphical abstract: Unlabelled Image Highlights: A type IA DNA topoisomerase with RNA topoisomerase and hydrolysis activity First analysis of all the steps of RNA topoisomerase activity viz. RNA binding, cleavage, strand passage and religation; an assay for RNA strand passage step First analysis of the reaction mechanism for RNA topoisomerisation. Two reaction paths for RNA topoisomerisation: proton relay route and 2′-OH group catalysed reaction. Active-site tyrosine required for all the catalytic steps with DNA and RNA; pH-dependent switch from RNA topoisomerisation to hydrolysis A new function for type IA topoisomerase–rRNA processing activity, a backup role to rRNA processing machinery